Membangun Keunggulan Kompetitif UKM melalui Ketangkasan Strategis dan Kemampuan Jaringan dalam Menghadapi Tantangan Lingkungan Bisnis yang Berfluktuasi - Arvel Liwang Savero; Aria Ganna Henryanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to delve deeper into the evolving challenges in the business environment, where the success of Small and Medium Enterprises (SMEs) in East Java in building competitive advantage often heavily relies on their ability to adeptly combine strategic agility and networking capabilities. The study seeks to comprehensively explore the direct impact of networking capabilities on enhancing the competitive advantage of SMEs in East Java, particularly amidst unstable business conditions. Additionally, it will investigate the vital role of strategic agility as a mediator facilitating the relationship between strategic agility, networking capabilities, and the competitive advantage of SMEs in the region, specifically adapting to the dynamics faced in the business environment. This study also plans to analyze the possibility that the influence of networking capabilities on the competitive advantage of SMEs in East Java can be mediated by effective strategic agility. Furthermore, in our endeavor to deepen this understanding, the research will explore how the level of turbulence in the business environment in East Java moderates the relationship between strategic agility and the competitive advantage of SMEs, with the hope of providing richer insights for entrepreneurs and stakeholders in the region.